Hijos de la Guerra - Fuchs, Alexandre (United States : Fly Films, 2007)
“Hijos de la Guerra” is a documentary about the history of the MS-13. Mara Salvatrucha (MS-13) is an international Hispanic street gang founded by Salvadoran civil war refugees in Los Angeles during the late 1980s, which the U.S government singles out as the fastest-growing and most violent gang in the country. The film explores the individual motivations behind gang membership and the ensuing explosion of fratricidal violence, as well as the complex role played by social and government policy in attempting to contain and yet unintentionally encouraging the spread of the gang. It addresses the motives and circumstances that have fueled this gang's ominous rise to power.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films